La experiencia del proceso enseñanza-aprendizaje de la enfermería comunitaria en el contexto de pandemia - Bel, Marcela (2020)
The objective of this article is to briefly present our experience as auxiliary teachers of the subject of Community Nursing, of the Bachelor of Nursing, in the context of the COVID 19 pandemic, describing the process of reflection, revision and adaptation of pedagogical strategies and didactic resources as a result of the conditions of virtuality. In this evolution, not only does the teaching-learning process challenge us as such, but also, considering the approach of the pandemic in the health-disease-care and care (PSEAC) processes in the training of nurses, a human resource of first need in these times, from an integral, interdisciplinary and community health perspective.